Assessing Freedom of Movement for Counterinsurgency Campaigns - Connable, Ben (RAND Corporation, 2012)
Freedom of movement (FoM) is the actual or perceived degree to which individuals or groups can move from place to place within a given environment or into and out of that environment. Focusing specifically on Afghanistan, this examination considers actual and perceived FoM for a range of groups and profiles the factors that influence them and affect data reporting in potentially misleading ways.